Pysical properties from common beans grains and castor bean hybrids regarding the cultivation system in Brazilian Mid-West (Research, Society and Development, 2020)
The aim of this study was to evaluate the physical properties of cultivars of common beans and castor bean hybrids, grow under intercropping and monocropping. The experimental outline applied was casual blocks in factorial scheme 4 x 2 + 6, with three replications. The treatments were constituted by grains coming from four cultivars of common beans (BRS Pérola, BRS Pitanga, BRS Esteio e BRSMG Realce), produced under intercropping system with two hybrid small sized castor cultivars (Tamar and Ag Ima 110204), added up by additional treatments constituted by genetic material of common beans and castor under monocropping. To evaluate the different treatments regarding the physical properties of the grains it has been considered the specific apparent mass, size (octagonal axles a, b and c), sphericity and circularity of grains. The cultivars intercropping for common beans with castor bean hybrids influenced the specific apparent mass of beans. None of the physical properties from castor grains were influenced by the cultivar intercropping of common beans. The monocropping of common beans and castor bean hybrids influenced the studied physical properties. Finally, the common beans grains held the greatest length under monocropping and greater sphericity and circularity when under intercropping with castor bean hybrids.